2017
DOI: 10.1097/scs.0000000000003664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Autologous Platelet-Rich Plasma in Nasal Pack on Postoperative Quality of Life

Abstract: According to the authors' study on PRP, the authors found out that by using PRP wound can be healed faster in early period of postoperative. It was seen with the authors' research that on postoperative early period crusts, bleeding and postoperative complaints are lesser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Platelet-rich plasma (PRP) contains a high number of platelets, growth factors (GF), and bioactive and neurotropic agents, crucial for wound healing and tissue repair. PRP has been used in various medical realms, such as orthopedic surgery, maxillofacial interventions, wound healing, and post-burn care (16,17).PRP has been studied in recent years as an alternative treatment for anosmia (12,18).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) contains a high number of platelets, growth factors (GF), and bioactive and neurotropic agents, crucial for wound healing and tissue repair. PRP has been used in various medical realms, such as orthopedic surgery, maxillofacial interventions, wound healing, and post-burn care (16,17).PRP has been studied in recent years as an alternative treatment for anosmia (12,18).…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies in the literature conducted in the field of otolaryngology, there are various studies demonstrating the positive effects of PRP on tissue regeneration in tympanic membrane perforations, after rhinoplasty operations, after septoplasty and endoscopic sinus surgery by being absorbed into nasal packings, in vocal cord injuries and acute facial nerve injuries ( 14 , 15 , 16 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found significant improvements in crusting and bleeding, as well as mucocilliary clearance [ 238 ]. Kuzucu et al conducted a study of 25 patients receiving standard nasal packs infused with PVRP and reported lower NOSE scores, less bleeding and crust formation compared to the control group, where the subjects received only saline nasal packing, confirming the hypothesis of accelerated healing in the septal and conchal mucosa [ 239 ].…”
Section: Use Of Plasma Rich With Platelets and Extracellular Vesicles...mentioning
confidence: 99%